Howard Gardner's Theory of Multiple Intelligences and Its Implications in Developing Student Potential in Islamic Religious Education Learning - Lulu Alwiyah; Fajar Syarif (Journal of Islamic Education Students (JIES), 2025)
Islamic Religious Education (PAI) aims to develop students’ potential holistically in order to form individuals who are faithful, morally upright, and balanced in intellectual, emotional, and spiritual dimensions. However, PAI learning practices often remain cognitively oriented and emphasize linguistic and logical–mathematical intelligence, thereby overlooking the diversity of students’ potentials. This study aims to examine the relevance of Howard Gardner’s Theory of Multiple Intelligences in Islamic Religious Education and to formulate its practical implications for student potential development. The study employed a qualitative descriptive approach using a Literature Review method. Data were collected from Gardner’s foundational works, Islamic primary sources, and relevant national and international journal articles published between 2020 and 2024. Data analysis was conducted through content analysis and conceptual synthesis. The findings indicate that the Theory of Multiple Intelligences is highly compatible with the Islamic concept of fitrah and the educational goal of developing insan kamil. The integration of MI into PAI enables comprehensive student development through religious project-based learning, reflective ibadah journaling, field-based activities, and authentic assessment. Therefore, Multiple Intelligences can serve as an effective pedagogical framework for enhancing the quality, inclusivity, and transformative impact of Islamic Religious Education.